GAMBARAN PENGELOLAAN DIABETES MELLITUS DARI PENDEKTAN NON-FARMAKOLOGI DI PUSKESMAS LAPAI KECAMATAN NANGGALO KOTA PADANG - Lilis Suryani; Endang Sepdanius (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2018)
Based on observations at the Lapai Health Center in Nanggalo Subdistrict, Padang City, there were 80 diabetics based on the data. Whereas only 1 club participated in gymnastics activities for 20 people. This diabetes exercise is held once a week. While the frequency should be 3-5 times per week. The purpose of this study was to determine the picture of diabetes mellitus management from the Non-pharmacological approach in Lapai Health Center, Nanggalo Sub-District, Padang City. This type of research is descriptive. The study population was 90 people. The sampling technique was taken by purposive sampling. The sample in this study amounted to 16 people. The technique of collecting data is by interviewing the manager, the food recall questionnaire and 24-hour daily activities of people with diabetes mellitus from the Non-Pharmacology approach in the Lapai Community Health Center, Nanggalo District, Padang City. The results of this study reveal that the management of diabetes mellitus from the Non-Pharmacological approach in the Lapai Health Center in Nanggalo SubDistrict, Padang City has been well implemented despite the weaknesses in the management. And the results of the study of a 24-hour food recall questionnaire of people with diabetes mellitus in Lapai Health Center, Nanggalo Subdistrict, Padang City, that 12 samples were classified as medium categories of 8 people (67%) and categorized as over 4 people (33%) while daily activities were classified low category 3 people (25%), classified as medium category 2 people (17%) and categorized as more than 7 people (58%).